Asian households’ dengue-related knowledge, attitudes, and practices: a systematic review - Ahmad Firdhaus Arham; Mohd Istajib Mokhtar; Nurhafiza Zainal; Mohamad Hasif Jaafar; Latifah Amin; Noor Sharizad Rusly; Mohd Fadhli Shah Khaidzir; Muhammad Firdaus Aziz; Nazri Muslim (Humanities & Social Sciences Communications)
Abstract Dengue remains the most prevalent vector-borne viral infection in the current century, contributing significantly to global morbidity and mortality. Despite being a preventable disease, the effectiveness of dengue control is strongly influenced by the level of knowledge, attitudes, and practices demonstrated by communities. This study systematically reviews and synthesises two decades of empirical research on household-level knowledge, attitudes, and practices concerning dengue in Asian countries. A systematic literature review was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses framework, which utilised major academic databases to identify publications from 2010 to 2022. The analysis revealed that although most respondents exhibited satisfactory knowledge and positive attitudes, their preventive practices remained inconsistent and suboptimal. These findings underscore the importance of sustained health education efforts and community engagement initiatives to enhance household-level awareness and behaviour towards dengue prevention.